Improving The Quality of Madrasas Through Financial Management - Gunawan Widjaja; Yuli Supriani; Khairul Nizam bin Zainal Badri; B.M.A.S. Anaconda Bangkara; Moh. Imam Ishomuddin Zuhri (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to analyse the planning, implementation, and supervision of education and financing management at MTs Al-Hikmah Plandaan Jombang using qualitative research with a case study approach. Data were collected through observation, interviews, and documentation. Furthermore, the analysis technique follows Hubberman's model, including reduction, presentation, and conclusion. The results are 1) All stakeholders are involved in the planning to improve the quality of education by using a novel approach to achieving the school's vision and goal. 2) The steps taken by MTs are to work together with all residents to improve madrasa performance by managing funds honestly, responsibly, and transparently. 3) Monitoring activities are appropriate because the internal and external assessment modifies the institution's progress.